Diversity of aphids (Hemiptera: Aphididae) associated with potato crop in Tizi-Ouzou (North of Algeria), with new records - Samia AIT AMAR; Karima BENOUFELLA-KITOUS (Acta Agriculturae Slovenica)
Aphids are among the phytophagous pests that cause serious damage to crop plants. In Northern Algeria, we have little information on their diversity. In this context, the study of the diversity of aphids was carried out in three regions of Tizi-Ouzou (North of Algeria) namely Tizi-Ouzou center, Tizi-Rached and Aghribs on the potato crop using yellow traps. The results showed a total richness of 65 aphid species, divided into 36 genera, 9 tribes and 8 sub-families, of which 11 species were identified for the first time in Algeria. These are Aphis coreopsidis (Thomas, 1878), Capitophorus hippophae (Walker, 1852), Cavariella theobaldi (Gillette & Bragg, 1918), Hyadaphis coriandri (B. Das, 1918), Macrosiphoniella linariae (Koch, 1855),Monelliopsis pecanis Bissell, 1983, Myzus hemerocallis Takahashi, 1921, Pseudoregma panicola (Takahashi, 1921), Rhopalosiphoninus staphyleae (Koch, 1854), Schizaphis eastopi Van Harten & Ilharco, 1971 and Ovatus inulae (Walker, 1849). The field located in the center of Tizi-Ouzou is the richest with 55 species, followed by the field of Tizi-Rached with 30 species, and 24 species have been recorded in Aghribs. During the sampling season, Hyperomyzus lactucae (Linnaeus, 1758) and Brachycaudus helichrysi (Kaltenbach, 1843)  are the most abundant species with 24.44 % and 21.8 % respectively. Three aphid species have been observed on potato leaves, namely Macrosiphum euphorbiae (Thomas, 1878), Aphis gossypii Glover, 1877  and Myzus persicae (Sulzer, 1776). The latter species was observed in all three study regions.